2018
DOI: 10.1007/s10811-017-1386-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect and removal of bisphenol A by two extremophilic microalgal strains (Chlorophyta)

Abstract: The effects and the removal efficiency of bisphenol A (BPA) on two extremophilic Chlorophyta strains, an alkaliphilic Picocystis and a thermophilic Graesiella, were assessed. BPA was shown to inhibit the growth and photosynthesis of both species, but to a greater extent for Graesiella. The growth IC 50 (4 days) was 32 mg L −1 for Graesiella andhigherthan75mgL −1 for Picocystis. Oxidative stress was induced in both strains when exposed to increasing BPA concentrations, as evidenced by increased malondialdehyde … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…In addition, increased activity of both CAT and GST was reported in Picocystis sp. exposed to 25, 50, and 75 mg/L of BPA [ 53 ]. As for GR, which is an enzyme involved in the glutathione cycle, we did not observe any effects of the tested compounds during exposure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, increased activity of both CAT and GST was reported in Picocystis sp. exposed to 25, 50, and 75 mg/L of BPA [ 53 ]. As for GR, which is an enzyme involved in the glutathione cycle, we did not observe any effects of the tested compounds during exposure.…”
Section: Discussionmentioning
confidence: 99%
“…when it was treated for 1, 2, 3, 4, and 5 days with 25, 50, and 75 mg/L; in addition, after 4 and 5 days, the APX activity was also increased by 10 mg/L of BPA. However, at 1 mg/L of BPA, no alterations in APX activity were recorded [ 53 ]. In the latter study, the activity of APX measured in Graesiella sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both species showed high BPA removal efficiencies, with Graesiella reaching 52.6% and Picocystis reaching 72% at 25 mg/L. The removal of BPA was mainly attributed to biodegradation by both species (Ben Ouada et al, 2018). Another study showed that a monoculture of Chlorella sorokiniana was able to partially remove BPA (Eio et al, 2015).…”
Section: Introductionmentioning
confidence: 97%